2020
DOI: 10.1021/acs.biomac.0c00039
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism and Multiple Melting Behavior of Bio-Based Poly(propylene 2,5-furandicarboxylate)

Abstract: Furandicarboxylate-based polyesters are considered an interesting class of bio-based polymers due to their improved properties with respect to the petrol-based terephthalate homologs. An in-depth analysis of the crystal structure of poly(propylene 2,5-furandicarboxylate) (PPF), after maximum possible removal of the catalyst, was carried out. The study disclosed that purified PPF presents two different crystalline phases after crystallization from the melt. Crystallizations at temperatures lower than 120 °C lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 66 publications
2
38
0
Order By: Relevance
“…45%) prevents the observation of a distinct glass transition, which should anyhow be present at 35–40 °C [ 33 ]. A double melting peak is observed for PGA, and it is tentatively ascribed to melting–recrystallization phenomena, which is typical of many polyesters (see [ 43 ] and reference therein).…”
Section: Resultsmentioning
confidence: 99%
“…45%) prevents the observation of a distinct glass transition, which should anyhow be present at 35–40 °C [ 33 ]. A double melting peak is observed for PGA, and it is tentatively ascribed to melting–recrystallization phenomena, which is typical of many polyesters (see [ 43 ] and reference therein).…”
Section: Resultsmentioning
confidence: 99%
“…Degrees of crystallinity of 25 and 33% for annealing and melt crystallization, respectively, have been reported [9,36,38,42], reaching 50% after solid state polycondensation (SSP) [13]. The coexistence of α-and β-crystal form (multiple melting endotherms), comparable to PET, was demonstrated for purified PEF by Righetti et al [34], as well as by Zheng and Pan [43], and was found to be correlated to catalysts acting as nucleation agents for the α-form.…”
Section: Introductionmentioning
confidence: 91%
“…The crystallization behavior and, especially, the investigation of the crystal structure of PEF by XRD have already been studied [8][9][10][11][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. Three different crystal polymorphs have been reported, i.e., α (triclinic), α', and β (monoclinic) structures [27,29,32,34].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations